Dans l’unité, la diversité : variations funéraires chez les groupes « sambaquiens » de la côte sud/sud-est du Brésil - Veronica Wesolowski; Renata Estevam (Brésil(s))
This article presents the evolution of scientific research on the shell mounds of the Brazilian south-southeast coast, focusing on the development of ideas that led to the construction of the current model of funerary sambaquis. We also seek to highlight gaps that require further research, and we propose that there are othernesses within the sambaquian society that built these shell mounds, and that their identity has evolved over time. Such evolutions can be revealed through a systematic study of the synchronic and diachronic variability of burial practices.